2014
DOI: 10.1021/ef5012808
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Liquefaction of the Microalgae Phaeodactylum tricornutum: Impact of Reaction Conditions on Product and Elemental Distribution

Abstract: The microalgae Phaeodactylum tricornutum was processed by hydrothermal liquefaction in order to assess the influence of reaction temperature and reaction time on the product and elemental distribution. The experiments were carried out at different reaction times (5 and 15 min) and over a wide range of temperatures (275-420 °C) using a batch reactor system. All fractions were quantified and analyzed in terms of specific elemental concentrations. The highest bio-oil yield (39 %) was obtained at 350 °C when using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 38 publications
(135 reference statements)
8
29
0
1
Order By: Relevance
“…While the multivalent ions demonstrated a tendency to precipitate under the studied hydrothermal conditions-which was reflected in the fact that calcium, magnesium, iron, and aluminum were mainly recovered in the HTL solid phase-the monovalent ions (K + , Na + ) remained dissolved in the HTL liquid phase. A similar tendency has been described in references [66,67]. The nitrogen that was recovered in the HTL liquid phase, which resulted from the degradation of proteins under hydrothermal conditions [15,26], was clearly higher for HTL-SPR-LP than for HTL-PSS-LP.…”
Section: Sample Idsupporting
confidence: 83%
“…While the multivalent ions demonstrated a tendency to precipitate under the studied hydrothermal conditions-which was reflected in the fact that calcium, magnesium, iron, and aluminum were mainly recovered in the HTL solid phase-the monovalent ions (K + , Na + ) remained dissolved in the HTL liquid phase. A similar tendency has been described in references [66,67]. The nitrogen that was recovered in the HTL liquid phase, which resulted from the degradation of proteins under hydrothermal conditions [15,26], was clearly higher for HTL-SPR-LP than for HTL-PSS-LP.…”
Section: Sample Idsupporting
confidence: 83%
“…Comparing the two biomasses with the coffee husk would yield a biofuel with the lowest sulphur content of 0.066%. The sulphur content expected for bio-oils is <0.05% m/m, where both biomass are above this value by which may require a process of desulfurization [22].…”
Section: Morphology By Scanning Electron Microscopymentioning
confidence: 89%
“…These may be due to the fact that in these treatments are conditions that give the water properties features that allow you to more easily carry depolymerization, hydrolysis reactions, and decomposition of the biomass [22]. On the band of the C=C aromatic notes a small shoulder in the region of 1700 cm -1 , which indicates that the biocarbon from hydrothermal reactions with carbonyl groups.…”
Section: Identification Of Functional Groups By Infrared Spectrometrymentioning
confidence: 99%
“…Vardon et al [12] obtained the conclusion that raw Scenedesmus had the highest yield of HTL bio-oil (45%) and about defatted Scenedesmus (36%) during the experiments of comparing HTL with slow pyrolysis. Christensen et al [28] processed Phaeodactylum by HTL in order to assess the influence of reaction temperature and reaction time on the product and elemental distribution and found that the highest bio-oil yield can reach 39% under the condition of 350 °C and 15 min. Tian et al [29] focused on the HTL of harvested algae from Dianchi in China and obtained the highest biofuel yield (18.4%) at 300 °C, 60 min and 20% solid concentration.…”
Section: Othersmentioning
confidence: 99%